2020
DOI: 10.1016/j.jspr.2020.101710
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hermetic containers in controlling paddy rice (Oryza sativa L.) storage insect pests

Abstract: Naturally infested paddy rice was used to compare the effectiveness of polypropylene bags and hermetic storage containers over 12 months of storage in a warehouse. Insect pest identification as well as the infestation level, percentage of damaged grain, weight loss, and moisture content were evaluated. Five insect species associated with stored rice were identified during the storage period, namely lesser grain borer (Rhyzopertha dominica), red flour beetle (Tribolium castaneum), rice/maize weevil (Sitophilus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The fluctuation of moisture content in hermetic storage systems has also been reported in previous studies and has been partly attributed to intermittent opening of the storage containers for grain sampling (Baoua, Amadou, Ousmane, Baributsa, & Murdock, 2014; Chigoverah & Mvumi, 2016; Covele et al, 2020). However, no sound explanation could be offered for the differences in the fluctuation of moisture content of the grain stored in Super Grain Bag when used alone and when associated with the polyethylene container, especially considering that, when used alone, the Super Grain Bag was perforated by insects after 4 months of storage.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The fluctuation of moisture content in hermetic storage systems has also been reported in previous studies and has been partly attributed to intermittent opening of the storage containers for grain sampling (Baoua, Amadou, Ousmane, Baributsa, & Murdock, 2014; Chigoverah & Mvumi, 2016; Covele et al, 2020). However, no sound explanation could be offered for the differences in the fluctuation of moisture content of the grain stored in Super Grain Bag when used alone and when associated with the polyethylene container, especially considering that, when used alone, the Super Grain Bag was perforated by insects after 4 months of storage.…”
Section: Discussionsupporting
confidence: 71%
“…On the contrary, the polyethylene container showed to be effective in limiting the multiplication of insects, achieving the best performance when combined with the Super Grain Bag, with only twofold increase in insect population after 180 days of storage. Covele et al (2020) also reported a reduction on insect population in paddy rice stored in high‐density polyethylene containers of different sizes for 12 months, while for grain stored in polypropylene bags the population of insects increased by eightfold over the storage period. Insect population increase in polyethylene container associated with Super Grain Bag is most likely to be a result of insect death making them easy to capture or to already existing larvae that developed to adult during the storage period.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Traditional methods of preserving and storing rice grains include the use of Silo, Nahu, Camphor, Dole, Motka, jute bags, Obeh and polypropylene bag [124]. The new method of storing rice grain, which includes hermetic bags such as the GrainPro, AgroZ, and Purdue Improved Crop Storage (PICS), have been reported [125][126][127]. The interest of farmers in hermetic bags has been sparked by the aim to cut rice grain storage losses due to insect pests and the difficulties (inefficacy) associated with current storage methods [128,129].…”
Section: Storage Of Paddymentioning
confidence: 99%